New essays in Japanese aesthetics - Nguyen, Minh, 1968- (Lexington Books, 2018)
This collection begins with an engaging historical overview of Japanese aesthetics and offers contemporary multidisciplinary and interdisciplinary perspectives on the artistic and aesthetic traditions of Japan and the central themes in Japanese art and aesthetics.